Comparing the Effects of Teaching based on the Learning cycle model, Collaborative method and usual method on the level of Academic Engagement and Attitude towards Learning in Experimental Sciences course for Eighth grade boys - Hassan Gharibi; Saber Tabarsharafi; Shahin Rahmyan; Saba Shafaeirad (رویکردهای نوین آموزشی)
This research was conducted with the aim of comparing the effects of education based on the learning cycle model, collaborative method and usual method on the level of academic engagement and attitude towards learning in the eighth grade experimental sciences course for boys. This research was a semi-experimental type with a pre-test-post-test design with a control group. The statistical population of the research included all eighth grade male students of the first year of high school in the academic year 1400-1401 in Gilan Gharb city, and 60 of them were selected as the research sample using the available sampling method. In order to collect data, Tinio's academic engagement questionnaire (2009) and Ekpiner et al. attitude towards science learning questionnaire (2009) were used. Also, multivariate analysis of covariance test was used to analyze the data. The results obtained from this research showed that after training based on the learning cycle method, the level of academic engagement and attitude towards learning of the group trained based on the learning cycle model had a significant decrease compared to the usual method in the post-test stage, and in other words, training based on the cycle model Learning compared to the usual method is more effective on the level of academic engagement and attitude towards learning in experimental sciences. According to the results of this research, it can be said that both the learning cycle intervention approach and the collaborative method have been effective in increasing academic engagement compared to the usual method, and the learning cycle intervention approach has been more effective than the collaborative method.Introduction:Attitude towards learning and how to deal with it, nowadays is one of the concerns of developed and developing educational systems. It seems that the speed and scope of progress in the field of science have influenced the human attitude towards the nature and method of learning. These influences are many and varied, one of them is academic engagement. One of the sources of strengthening the attitude towards learning and academic engagement is teaching-learning methods. Collaborative learning is a type of learning and approach that are used to perform a variety of educational activities and tasks, including learning different courses to completing research projects. Among other teaching methods that is compatible with science education and appropriate in this field, is the learning cycle model (Alaghemand, 2018). The evidence shows that these methods can help students to internalize educational materials and able to use their discoveries in new social situations (Aydisheh & Gharibi, 2015). The existing researches in this field primarily examine the effect of a teaching method on the mentioned variables and the difference between these two teaching methods has not been compared. present research investigated the following hypotheses: 1- There is a difference between the averages of the post-test of academic engagement in the three groups of education using the learning cycle method, collaborative method, and the usual method. 2- There is a difference between the post-test averages of attitude to learning in the three groups of teaching by the learning cycle method, teaching by the collaborative method and the usual method.Research methodology In terms of implementation, this research was a semi-experimental method of pre-test-post-test type with a control group. The statistical population included all male students of the eighth grade of the first period secondary school in the city of Gilan Gharb, whose number was 723. Random sampling was available. The sample size was calculated at 60 people using the available sampling method and they were randomly assigned to two experimental groups (two groups of 20 people) and a control group (20 people). Intervention program was designed and implemented according to the variables and research literature. It was carried out on experimental groups. In order to homogenize the experimental and control groups and to have similar background conditions in terms of social status and the level of access to facilities, all three groups were selected from the same school. The criteria for entering the study included: being a first-year high school student, willingness to participate in the research, and the criteria for exiting the study included: unwillingness to participate in the research. Data analysis was done using multivariate covariance and SPSS version 23 software. To collect data, questionnaires of academic engagement (Tinio, 2009) and attitude to learning (Ecpiner, 2009) were used. One of the classes was taught by the learning cycle method, the other class was taught by the cooperative method, but the third group, the control group, did not receive any training and continued their education in the usual way of schools.Research findingsTable 1: Results of one-way covariance analysis to investigate the mean difference between the experimental and control groups in the variables of academic engagementStatistical powerEta coefficientSignificant   levelFmean square msdegree of freedomdfsum of squaresSsSource of changesVariable10/5490/001*31/6593/88193/88pre-testAcademic0/9930/4950/001*12/7332/76275/52groupengagementTable 2. The results of adjusted averages for the variable of academic engagementStandard errorAverageGroupVariable0/55124/52Collaborative methodAcademic0/54526/87Learning cycleengagement0/54722/4The usual method Table 3:  The results Bonferroni's test to compare means scores academic engagement in three groupsSignificant levelstandard errorDifference of meansgroupscomparisondependent variable   groupgroup 0/0050/7362/349Learning cycleCollaborative methodAcademic*0/0010/7473/879The usual method engagement**0/0090/7712/53The usual methodLearning cycle Table 4: Results of one-way covariance analysis to investigate the mean difference between the experimental and control groups in the variables of attitude to learningStatistical powerEta coefficientSignificant levelFmean square msdegree of freedomdfSum of squaresSsSource of changesVariable10/4380/001*20/5478/71178/71pre-testAttitude to0/8820/3840/001*11/6212/65264/31grouplearningTable 5: The results of adjusted averages for the variables of attitude to learningStandard errorAverageGroupVariable0/68146/74Collaborative methodAttitude to0/23549/42Learning cyclelearning0/35644/61The usual method Table 6: The results Bonferroni's test to compare means scores attitude to learning in three groupsSignificant levelstandard errorDifference of meansgroupscomparisondependent variable   groupgroup 0/0050/7362/432Learning cycleCollaborative methodAttitude to*0/0010/7473/456The usual method learning**0/0090/2301/235The usual methodLearning cycle Discussion and conclusion:The results showed that learning cycle teaching and collaborative teaching have an effect on academic engagement and attitude towards learning. It seems that in the collaborative method and the learning cycle, students' cognitive constructions become imbalanced through facing the real problems of the class and pondering over them. In the learning cycle model class, learners interact with activities at each stage, discuss questions and share their knowledge with each other. Also, in the collaborative method, the sense of integration and high interaction leads to more practice and repetition, improves learning and increases students' academic enthusiasm. The results of comparing the effectiveness of the methods showed that both the learning cycle intervention approach and the collaborative method have been effective in increasing academic engagement compared to the usual method, but the learning cycle intervention approach has been more effective than the collaborative method. In the explanation, it can be said that the agency combined with the interaction of learners together in cooperative learning has an effect on students' cooperation, self-reliance, the motivation to participate in solving challenging problems, increasing cognitive, metacognitive, motivational and cooperative skills, and the feeling of belonging to the group. Another finding of the research about the difference between the effectiveness of learning cycle teaching, collaborative teaching and conventional teaching on the level of attitude towards learning showed that the difference was significant. Also, the learning cycle intervention approach was more effective than the collaborative method. It can be said that students who are taught with the learning cycle approach pay attention to time management, checking goals and making connections between new and previous material. It is suggested to use samples including female students and a wider geographical area and other communities with different cultural-social backgrounds in future researches.